(untitled) (Swiss Medical Weekly, 2021)
AIMS The aim of this study was to analyse the demographics, risk factors and in-hospital mortality rates of patients admitted with coronavirus disease 2019 (COVID-19) to a tertiary care hospital in Switzerland. METHODS In this single-centre retrospective cohort study at the University Hospital Basel, we included all patients with confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection hospitalised from 27 February 2020 to 10 May 2021. Patients’ characteristics were extracted from the electronic medical record system. The primary outcome of this study was temporal trends of COVID-19-related in-hospital mortality. Secondary outcomes were COVID-19-related mortality in patients hospitalised on the intensive care unit (ICU), admission to ICU, renal replacement therapy and length of hospital stay, as well as a descriptive analysis of risk factors for in-hospital mortality. RESULTS During the study period we included 943 hospitalisations of 930 patients. The median age was 65 years (interquartile range [IQR] 53–76) and 63% were men. The numbers of elderly patients, patients with multiple comorbidities and need for renal replacement therapy decreased from the first and second to the third wave. The median length of stay and need for ICU admission were similar in all waves. Throughout the study period 88 patients (9.3%) died during the hospital stay. Crude in-hospital mortality was similar over the course of the first two waves (9.5% and 10.2%, respectively), whereas it decreased in the third wave (5.4%). Overall mortality in patients without comorbidities was low at 1.6%, but it increased in patients with any comorbidity to 12.6%. Predictors of all-cause mortality over the whole period were age (adjusted odds ratio [aOR] per 10-year increase 1.81, 95% confidence interval [CI] 1.45–2.26; p <0.001), male sex (aOR 1.68, 95% CI 1.00–2.82; p = 0.048), immunocompromising condition (aOR 2.09, 95% CI 1.01–4.33; p = 0.048) and chronic kidney disease (aOR 2.25, 95% CI 1.35–3.76; p = 0.002). CONCLUSION In our study in-hospital mortality was 9.5%, 10.2% and 5.4% in the first, second and third waves, respectively. Age, immunocompromising condition, male sex and chronic kidney disease were factors associated with in-hospital mortality. Importantly, patients without any comorbidity had a very low in-hospital mortality regardless of age.